Effects of Clostridium butyricum- and Bacillus spp.-Based Potential Probiotics on the Growth Performance, Intestinal Morphology, Immune Responses, and Caecal Microbiota in Broilers - Xinfu Zeng; Qing Li; Caimei Yang; Yang Yu; Zixian Fu; Huixian Wang; Xiaoyan Fan; Min Yue; Yinglei Xu (MDPI AG, 2021)
We aimed to investigate the effects of Clostridium butyricum-, Bacillus subtilis-, and Bacillus licheniformis-based potential probiotics on the growth performance, intestinal morphology, immune responses, and caecal short chain fatty acids (SCFAs) and microbial structure in broiler chickens. Three treatment groups containing a total of 1200 one-day-old AA broilers were included: birds fed with a basal diet only (Con), birds fed with added 1010 probiotics cfu/kg (ProL), and birds fed with added 1011 probiotics cfu/kg (ProH). The dietary probiotics significantly improved the final and average body weights and serum immunoglobulins A, M, and Y. The probiotics also enhanced the ileal morphology and improved the caecal acetate, butyrate, and propionate contents. Furthermore, 16S rRNA sequencing revealed that dietary compound probiotics modulated the caecal microflora composition as follows: (1) all birds shared 2794 observed taxonomic units; (2) treatment groups were well separated in the PCA and PCoA analysis; (3) the relative abundance of Parabacteroides, Ruminococcaceae_UCG-014, Barnesiella, Odoribacter, [Eubacterium_coprostanoligenes_group], [Ruminococcus]_torques_group, and Butyricimonas significantly varied between treatments. The compound probiotics improved the growth performance, serum immune responses, the ratio of ileal villus height to crypt depth, and major caecal SCFAs in broiler chickens. The dietary C. butyricum-, B. subtilis-, and B. licheniformis-based probiotics improved overall broiler health and would benefit the poultry industry.